STRATEGY MANAGEMENT ANALYSIS USING SWOT ANALYSIS IN INCREASE SALES AT AFECTO COFFEE SHOP - Aldri, Farhan; Nugraha, Harry (Universitas Islam Lamongan, 2024)
The competition of the business world seems to increase by seeing the competition that occurs in the increasingly competitive coffee shop industry, the role of strategy is needed in achieving business goals and the need to develop effective strategies in the midst of fierce competition in the coffee shop industry. This research is qualitative research using descriptive methods. The type of approach used is a case study. Data collection techniques are carried out using observation, interview, questionnaire and documentation methods. While data analysis uses SWOT analysis techniques and descriptive analysis. Based on the results of the study showed that based on IFAS analysis obtained with an IFAS score of 3.41 and EFAS score obtained with a score of 1.30, this result shows that Afecto can increase sales. Afecto's position in a strong state can be seen from the level of opportunity greater than the threat he faces and the level of strength is higher than the level of weakness